Final results of a self-apposing paclitaxel-eluting stent fOr the PErcutaNeous treatment of de novo lesions in native bifurcated coronary arteries study - Naber, Christoph K.; Pyxaras, Stylianos A.; Nef, Holger; Ijsselmuiden, Alexander J.; Briguori, Carlo; Schlundt, Christian; Wykrzykowska, Joanna; Eberli, Franz R.; Moellmann, Helge; Galatius, Soren; Rieber, Johannes; Commeau, Philippe; et al. (EuroIntervention, 2016)
AIMS: We aimed to evaluate the long-term safety and efficacy of the STENTYS self-apposing paclitaxeleluting stent (STENTYS-PES) in bifurcation lesions in routine clinical practice. METHODS AND RESULTS: The primary endpoint of the study was the composite major adverse cardiac events (MACE: cardiac death, myocardial infarction, clinically driven target lesion revascularisation, or emergent bypass surgery) assessed at six months after enrolment. This was reported in 21 patients (10.1%), mainly due to clinically driven target lesion revascularisation (TLR). At 12 months, 27 patients experienced MACE (13.0%). CONCLUSIONS: The long-term results of OPEN II show that the STENTYS-PES is safe and effective in the treatment of all-comers with coronary bifurcation lesions.
EVALuna2:12099